2014
DOI: 10.1016/j.jmb.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Two Novel Missense Mutations in the GDF5 Proregion That Reduce Protein Activity and Are Associated with Brachydactyly Type C

Abstract: Growth and differentiation factor 5 (GDF5) plays a central role in bone and cartilage development by regulating the proliferation and differentiation of chondrogenic tissue. GDF5 is synthesized as a preproprotein. The biological function of the proregion comprising 354 residues is undefined. We identified two families with a heterozygosity for the novel missense mutations p.T201P or p.L263P located in the proregion of GDF5. The patients presented with dominant brachydactyly type C characterized by the shorteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Point mutations in the proregion of GDF5 can cause skeletal malformations such as brachydactyly C. Two exchanges, T201P and L263P, have recently been identified, and their functional characterization demonstrated a loss of function of the proform in a chicken micromass assay . Notably, the two exchanges are located in a protease‐resistant core domain that has been identified previously .…”
Section: Resultsmentioning
confidence: 80%
“…Point mutations in the proregion of GDF5 can cause skeletal malformations such as brachydactyly C. Two exchanges, T201P and L263P, have recently been identified, and their functional characterization demonstrated a loss of function of the proform in a chicken micromass assay . Notably, the two exchanges are located in a protease‐resistant core domain that has been identified previously .…”
Section: Resultsmentioning
confidence: 80%
“…, mAcvr1 R206H dLBD [22], mBmpr1a (also known as Alk3) and mBmpr1b (also known as Alk6) all in pCS2+ [23]. For generation of the mTgfβr1 c.a.…”
Section: Expression Plasmidsmentioning
confidence: 99%
“…The study revealed that the mutations affected the thermodynamic stabilities of the protein variants. All three exchanges caused a loss of function with regard to chondrogenesis (Stange et al, 2014(Stange et al, , 2015. Another natural amino acid exchange (R380Q) within the proregion of GDF5 had been detected earlier in a patient family diagnosed with Brachydactyly A2, a clinically different malformation of the digits (Ploger et al, 2008).…”
Section: Disease-associated Mutations In the Tgf-β/bmp Proregionsmentioning
confidence: 97%
“…The important roles of the proregions during biogenesis of the mature growth factors is highlighted by several reports that describe natural mutations in the proregion of human GDF5 (Table 1). Interestingly, three point mutations were identified that lie within the DNA encoding the core fragment of the GDF5 proregion and led to skeletal malformations in fingers and toes, classified as Brachydactyly C (Stange et al, 2014(Stange et al, , 2015. The biochemical and structural effects of the exchanges have been analysed in the recombinant purified mutant proteins .…”
Section: Disease-associated Mutations In the Tgf-β/bmp Proregionsmentioning
confidence: 99%